A marketing study and plan for the introduction of the fuel cell hybrid vehicle in the Philippines the Toyota Prius, wait and see! - Ante, Michael Andrew S.; Cruz, Edison (Quezon City University of the Philippines Diliman, 2008)
The Toyota Prius is one of the most celebrated success story in the global Automotive Industry. Since its launch in the 1990s, it has gained popularity in various areas of automotive competencies. Being the pioneer and the dominant design, it has set the global standards for the Fuel Celled Hybrid Vehicles. In its 10th year in 2007, it has generated outstanding record sales of more than 1,000,000 units produced, which is so far the highest record sales achieved by a FCHV and is a long way from the achievements of other Hybrid brands. Not to mention, in the US, Toyota Prius constitutes more than 40 percent of the total automotive market sales in 2007. Its success can be traced back as it is recognized as one of the most efficient vehicle and the number 1 eco-friendly car mass produced and available in the market. This was made possible due to the high technology embedded in the vehicles design. Fuel economy is improved as much as 50 percent and pollution and emission reduced to significantly low levels. Despite its global success, it is not a common sight in the Philippines. Toyota Motor Philippines, is the number 1 automotive company in the country, but why is the TMP not pushing for Prius sales? When will TMP launch its Toyota Prius for Filipinos to adopt and enjoy? These are some of the questions the author would seek to address in the paper. As a bold primer to the paper's contents, the sale of the Toyota Prius in the Philippine market seems far from being a reality. The country's socio-political environmental factors such as government regulations on importation and tax exemptions, product costing, technology appropriation, and other issues remain to be steady barriers in launching the Toyota Prius. At this point the most that the motoring public can anticipate is to see these magnificent technologies inside malls and motorcades as display and not inside Toyota Dealerships for sale. Given the current hindrances, the author will create a Toyota Prius Marketing Plan, to anticipate its launch in the Philippines. Due to its countless possible contributions, such as economic growth, environmental friendliness, and a technology leap frog for the automotive industry, the Toyota Prius should be launched in the country despite the hindrances of selling the Hybrid vehicle. Aside from the barriers aforementioned, the paper will, likewise, provide a description of Fuel Celled Hybrid Vehicle (FCHV) technology, the Toyota Prius as a product, and its significance and possible contributions to the country. An environmental scan will be presented using the SWOT analysis and Michael Porter's 5 Forces analysis together with the discussion on the target market, embedded technology, legal and regulatory requirements, and the socio-cultural point of view. The majority of the paper will cover a comprehensive Marketing Plan guided by the global competitive strategy adopted by Toyota Motor Corporations Japan. TMP will adopt the global direction and create its own Philippine Marketing strategy that will focus on the Prius's pre-launch in the Philippine Market. The strategy application areas will focus on the Toyota Prius's product and pricing position with respect to the product's current position in the technology adoption curve. A comprehensive product description, a communication and promotion strategy, a comparative financial study, and other topics will likewise be discussed. These topics and more will be studied, discussed and presented to the readers to provide a clear picture of the study, especially to those innovators and early adopters who are participating the launch of Toyota's excellent Fuel Celled Hybrid Vehicle, the Toyota Prius. For now, let us all, "Wait and See..."
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Toyota Prius; Fuel cell industry -- Philippines; Fuel cell hybrid vehicle